Clinical Characteristics of Juvenile Idiopathic Inflammatory Myopathy and Comparison With Adult Patients: Analysis From a Multicentric Cohort in Spain. Issue 1 (25th January 2021) - Loarce-Martos, Jesús; Larena, Carmen; Blázquez, M. Ángeles; Joven, Beatriz E.; Carreira, Patricia E.; Martínez-Barrio, Julia; Monteagudo, Indalecio; López-Longo, Francisco Javier; Ruiz, Lucía; López-Robledillo, Juan Carlos; Almodóvar, Raquel; Llorente, Irene; et al.
Background/Objective: Few studies have been published focusing on the differences between juvenile idiopathic inflammatory myopathy (JIIM) and adult IIM. This study aimed to describe the characteristics of JIIM main subgroups (juvenile dermatomyositis [JDM] and juvenile polymyositis [JPM]) and to compare their differences with adult IIM subgroups (adult DM and adult PM). Methods: This study reviewed the medical records of patients from the REMICAM cohort, a multicentric longitudinal study carried out in patients with IIM, followed up between 1980 and 2014 in 12 hospitals in Madrid, Spain. Patients with definite or probable JPM, JDM, adult DM, and adult PM according to the modified Bohan and Peter criteria were selected. We compared the characteristics between JDM and JPM, and between JIIM and adult IIM. Results: Eighty-six juvenile patients (75 JDMs and 11 JPMs) and 283 adult patients (133 DMs and 150 PMs) were included. Compared with patients with JDM, patients with JPM were older at diagnosis, had more fever and arthritis, and were less frequently treated with disease-modifying antirheumatic drugs (these differences were not statistically significant). Compared with patients with adult DM, those with JDM presented more frequently with calcinosis (33.8% vs 6.9%, p < 0.0001) and had less severe infections (4.3% vs 23.4%, p < 0.0001), malignancies (1.3% vs 25.6%, p < 0.0001), and mortality (3.5% vs 33%, p < 0.0001). Patients with JDM were treated less frequently with azathioprine (10.8% vs 44.7%, p < 0.0001). Conclusions: Our findings confirm that JIIMs are a heterogeneous group of diseases with relevant differences compared with adult IIMs.